Woodcutting path southwest of Keels - Catherwood, Kristin (2012)
This path may be more than a century old, and would have been made by residents of Keels to facilitate the transport of wood cut from the forest bordering Keels to the south and west back to the community where it was used as firewood. The path is still used for the same purpose, though instead of horse-pulled carts or slides, it is now mainly used by ATVs. It is also a pedestrian path leading to the Blue Point picnic site approximately 1 km west of Keels.